Pneumocephalus as a Complication of Regional Epidural Block Due to Lumbosacral Radiculopathy - Ramírez González, Alberto Dariel; Ricardo Colomar, Grisel; Betancourt Plaza, Iliovanys (Revista Cubana de Medicina, 2023)
Introduction: Pneumocephalus (synonym: aerocele or intracerebral pneumatocele), is defined as the presence of gas within any of the intracranial compartments (intraventricular, intraparenchymal, subarachnoid, subdural and epidural). Objective: To describe the clinical findings, complementary studies, therapeutic conduct and evolution of a case with pneumocephalus as a complication of regional epidural block due to lumbosacral radiculopathy Case presentation: A 57-year-old male patient was presented who began with a sudden episode of disorientation, psychomotor excitability and tonic-clonic seizures, following an epidural injection of methylprednisolone as an analgesic method. Conclusions: The case presented exhibited non-specific neurological manifestations, the sudden appearance after the invasive procedure raised suspicion of an acute neurological event or thromboembolic phenomenon. Complementary studies such as simple cranial computed axial tomography, allowed its diagnosis to have a consistent conduct. The conservative management of pneumocephalus as a complication of the use of epidural anesthesia constituted an effective therapeutic approach and had an impact on the patient's satisfactory evolution.